(untitled) (Journal of Bangladesh Academy of Sciences, 2020)
A field experiment was conducted to evaluate the effect of 2,3,5-triiodobenzoic acid (TIBA) at 0, 10, 20, 30 and 40 ppm on the morphological and root anatomical changes of lentil (Lens culinaris Medik. cv. BARI Mosur-7). Foliarly applied TIBA decreased plant height significantly with the increasing concentrations of TIBA. Significantly maximum number of branches and leaves per plant were recorded due to 10 ppm TIBA treatment. Leaves were darker green in plants receiving 10 ppm TIBA due to high chl-a, -b and low carotenoid contents compared to control. Ten ppm TIBA increased root length significantly and root diameter non-significantly than the control plants. Root diameter in plants treated with 10 ppm TIBA increased due to the increase in the width of the cortex, decrease in vessel diameter and enhancement of the formation of more secondary xylem vessels. Journal of Bangladesh Academy of Sciences, Vol. 43, No. 2, 107-112, 2019